Seksualitas Tokoh Utama Novel Falling Karya Rina Suryakusuma: Kajian Psikoseksual - Hanita Yunia Sari; Widyatmike Gede Mulawarman; Alfian Rokhmansyah (Center of Language and Cultural Studies, 2021)
This study aims to reveal changes in sexual orientation, causes, and impacts of changes in the sexual orientation of the main character in Rina Suryakusuma's novel Falling. This study will examine a novel with the theme of female homosexuals using psychosexual theory. This study uses a qualitative research type. The data are in the form of quotations or story fragments obtained from the Falling novel. Reading and note-taking techniques were used as data collection techniques. The reading technique is the first step used to understand the story and find data. The note-taking technique is used to record data that has been obtained in the previous technique. The data taken is the data needed to answer the problem formulation that has been set. The data is then analyzed using a predetermined theory. From the results of the analysis then a conclusion is drawn. The results showed that, first, the main character's orientation changes due to physical contact and emotional attraction to the same sex. Second, the factors that cause changes in the sexual orientation of Carly's character, namely the inhibition of Carly's psychosexual development at the phallic, latent, and genital stages; parenting; traumatic experiences; and feelings of boredom towards heterosexual relationships. Third, the impact of changes in the main character's sexual orientation, namely: the character's decision to become a lesbian who does not get support will be shunned from his family and people around him; changes in sexual orientation affect the mindset of the perpetrator to come out.